Iterative Methods for Solving Nonlinear Equations - Abhinav Jajwal, Anjana Rajoria (Mathematical Statistician and Engineering Applications, 2021)
Solving such problems often involves the Newton technique. Nonlinear equations are the go-to solution for most issues in mathematics and engineering. Analysis of numerical data is a method of solving mathematical issues. As a result of the stimulating and fruitful research being done in this field, we propose and examine a novel iterative strategy for resolving nonlinear equations. The numerous methodologies, which are employed by researchers to produce higher order iterative methods such as functional approximation, sampling, composition, geometric and Adomian approaches, are given. the iterative techniques for finding multiple roots several iterative methods to solve systems of nonlinear equations are developed.